An Interpretation Approach for in FieldMeasured Dissipation Factor Values of MV Cable Lines - Freitag, Christian; Mladenovic, Ivana; Weindl, Christian (11th IEEE International Conference on Solid Dielectrics, 2013)
In modern power utilities attention is especially directed to the condition determination of the network's electrical equipment, with the purpose of supporting the condition oriented asset management and maintenance strategies. In medium voltage (MV) networks, cables require the biggest investment capital. In order to point out the most suitable diagnostic parameters and their limits, a long lasting accelerated and artificial ageing experiment on MV paper insulated lead covered (PILC) cables was performed. The in this way determined dependencies of the diagnostic parameters on voltage, temperature and condition of the cables, as well as characteristic values and regarded failure probability play an immense role in the determination of cables' condition in field measurements. Still, the diagnostic criterion (e.g. in case of dissipation losses comparison of: absolute value, hysteresis, dependency on testing voltage) could significantly influence the final diagnostic statement. In addition, the recorded values have to be evaluated regarding the composition of the cable line. This problematic will be shown in the article and discussed on several exemplar field measurement
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.leen.aninte
Keywords: Power cables; Voltage measurement; Power cable insulation; Correlation coefficient; Dielectrics; Temperature measurement